Gene editing particle system as a therapeutic approach for drug-resistant colorectal cancer - Ryu, Jee Yeon; Choi, You Jung; Won, Eun Jeong; Hui, Emmanuel; Kim, Ho Shik; Cho, Young Seok; Yoon, Tae Jong (Nano Research, 2020)
The epidermal growth factor receptor (EGFR) pathway plays an important role in the progression of colorectal cancer (CRC). Anti-EGFR drugs based on antibodies have been widely used for treating CRC through inducing the cell death pathway. However, the majority of CRC patients will inevitably develop drug-resistance during anti-EGFR drug treatment, which is mainly caused by a point mutation in the KRAS oncogene. We developed a nanoliposomal (NL) particle containing the Cas9 protein and a single-guide RNA (sgRNA) complex (Cas9-RNP), for genomic editing of the KRAS mutation. The NL particle is composed of bio-compatible lipid compounds that can effectively encapsulate Cas9-RNP. By modifying the NL particle to include the appropriate antibody, it can specifically recognize EGFR expressing CRC and effectively deliver the gene-editing complexes. The conditions of NL treatment were optimized using a KRAS mutated CRC in vivo mouse model. Mice with KRAS-mutated CRC showed drug resistance against cetuximab, a therapeutic antibody drug. After treating the mice with the KRAS gene-editing NL particles, the implanted tumors showed a dramatic decrease in size. Our results demonstrated that this genomic editing complex has great potential as a therapeutic carrier system for the treatment of drug-resistant cancer caused by a point mutation. [Figure not available: see fulltext.]
Keywords: Colorectal cancer; Drug resistance; KRAS mutation; nanoliposome; Palindromic; clustered regularly interspaced short palindromic repeat and associated Cas9 nuclease (CRISPR/Cas9); colorectal cancer; drug-resistance; KRAS mutation; nanoliposome